Preliminary results from CdTe spectrum detectors - Do?ru, Mahmut (My University, 1997)
A few CdTe detectors of different thicknesses and active areas have been studied for gamma-ray spectroscopy. The current of the detectors is low even at high bias voltages. The charge collection efficiency (cce) up to 98 % for the detection of 60 keV gamma radiation from 241Am and up to 85 % for the detection of 122 keV gamma radiation from 57Co sources have been obtained. The measured cce is good agreement compared with previously calculated cce using a model which includes trapping effects. The detector radiation count rate increases dramatically with applied bias. Polarization effect is produced by radiating the detectors for extended time with 57Co source. Decreases in count rate is very slow. © Tübi?tak.